2017
DOI: 10.7763/ijet.2017.v9.965
|View full text |Cite
|
Sign up to set email alerts
|

A Hierarchical Document Clustering Approach with Frequent Itemsets

Abstract: Abstract-In order to effectively retrieve required information from the large amount of information collected from the Internet, document clustering in text mining becomes a popular research topic. Clustering is the unsupervised classification of data items into groups without the need of training data. Many conventional document clustering methods perform inefficiently for large document of collected information and require special handling for high dimensionality and high volume. We propose the OCFI (Ontolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…By utilizing multi-node collaboration and resource distribution, this technique may effectively cut energy consumption. Routing in clusters solutions there have put out in the written word to reduce energy consumption [22][23][24]. The low energy adaptive clustering hierarchy (LEACH) method created in the literature [22] to spread the energy burden among the network's sensors equally.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…By utilizing multi-node collaboration and resource distribution, this technique may effectively cut energy consumption. Routing in clusters solutions there have put out in the written word to reduce energy consumption [22][23][24]. The low energy adaptive clustering hierarchy (LEACH) method created in the literature [22] to spread the energy burden among the network's sensors equally.…”
Section: Related Workmentioning
confidence: 99%
“…An improved LEACH method for mobile sensor networks is described in [23]. The system uses fuzzy inference techniques to reduce packet loss while simultaneously lengthening the network lifetime.…”
Section: Related Workmentioning
confidence: 99%
“…There has also been a lot of research which is related, but had a different scope. The authors of [ 11 ] for example discussed document clustering in the context of search queries, whereas [ 12 ] discussed the topic of hierarchical clustering. In the field of bioinformatics or life science informatics, the automatic classification and recognition of texts according to their medical, chemical or biological entities is in the scope of researchers (see [ 13 ], [ 14 ] or [ 15 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors, e.g. Hirsch et al, cover related problems like clustering in the context of search queries [6], whereas Lee et al work on the field of hierarchical clusterings [7]. Thus, it can be concluded that focusing only on graph clustering is a novel approach and the generalization of soft document clustering introduced in [1] provides new insights into document clustering -or clustering in general -from the developed graph theoretical toolbox .…”
Section: Introductionmentioning
confidence: 99%